MEKTEPLERDE ATOM FIZIKASÍ BÓLIMIN OQÍTÍWDÍ JETILISTIRIW JOLLARÍ (Mektep fizika muǵallimlerine metodikalıq járdem) - Jumamuratov, A.J.; Kalilaev, F.K. (SCIENCE and SOCIETY, 2022)
It is analyzed the methods of increasing the effectiveness of teaching in atomic, nuclear and elementary particle physics in schools with the help of innovative technologies.